"When I act consciously, I can see a brighter world around me": preservice teacher readiness to support transformative sustainability learning. Issue 11 (10th October 2022) - Wakefield, Wendy; Weinberg, Andrea E.; Pretti, Esther; Merritt, Eileen G.; Trott, Carlie
Abstract: Teacher education is pivotal to advancing pedagogies, practices, and content knowledge that promote sustainability literacy in formal education settings. To explore preservice teachers' (PST) readiness to implement transformative sustainability learning with elementary (i.e. kindergarten to 6th grade) students, we analyzed unit plans created by PSTs in a sustainability teacher education course. Within these units, we looked for evidence of content and pedagogy which (i) embraces the complexity of human-environmental interactions, (ii) advances sustainability literacy by enlisting both knowledge and engagement, and (iii) mobilizes action in local and global contexts to advance social and environmental justice aims. We describe the range of topics and analyze the rationales and learning activities through the 'Head, Hands and Heart' framework for transformative sustainability learning. We found that, though most PSTs integrated learning objectives and activities intended to engage students' heads, hearts, and hands into their units, they struggled to embrace the complexity of sustainability issues and to engage students in justice-focused action. We provide three recommendations for preservice teacher education to increase PSTs' readiness to implement transformative sustainability learning.